Should we rely on forecasts of prices or returns? The short term approach - Majerowska, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Investors make their decisions on the basis of the information coming from the market. The main features of assets are prices and investment risk. The rates of return are calculated based on the prices. For modelling the returns, capital asset pricing models can be applied; for the prices, methods of technical analysis could be taken into account. The purpose of this paper is to evaluate both approaches. First – financial modelling of the assets’ returns, and the second – the analysis of the assets’ prices. In order to verify the effectiveness of the forecasting processes, forecasts and ex-post type forecasting errors were calculated. The empirical analysis is based on the stock prices of ten food companies traded on the Warsaw Stock Exchange. The traditional CAPM and the extension of the CAPM by the GARCH(1,1) process are in use. As the technical analysis tool for price modelling, three period moving averages are calculated. The obtained results allow indicating the superiority of modelling the returns, in terms of short-term forecasting. Unfortunately, the hypothesis about the advantage of the application of GARCH for modelling, and then for forecasting, must be rejected
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 187-200
Keywords: modelling returns; CAPM with GARCH; moving average; modelowanie stóp zwrotu; CAPM z efektem GARCH; średnia ruchoma